PEMBAHARUAN PEMETAAN WILAYAH DESA CILEDUG KECAMATAN SETU BEKASI MENGGUNAKAN ARCGIS - Wasita, Andi; Novita, Dila; Nadhirah Qintharah, Yuha (An-Nizam, 2025)
Location mapping is an essential representation used to describe the Earth’s surface through a projection system that allows spatial data to be displayed in a flat form. A map provides critical information on size, area, distance, and direction of a specific location. This community service program focused on creating an updated location map of Ciledug Village, Setu District, Bekasi Regency, with the primary objective of comparing the 2025 administrative map to the 1994 version. The activity aimed to identify territorial expansions, spatial changes, and variations in distance that have occurred over time, thereby offering valuable insights into regional development. The implementation method consisted of several stages, namely observation, systematic data collection, and community outreach. Observations were conducted to assess the physical and administrative boundaries of the village, while data collection provided quantitative evidence of spatial changes. Outreach sessions involved discussions with village officials to ensure that the updated mapping product could be effectively utilized for governance and planning.The results of this program revealed that the village government of Ciledug is now better equipped to recognize regional transformations and make more informed decisions in village planning and development. Furthermore, the newly created administrative map functions as an accurate, comprehensive, and strategic document that can guide spatial management, infrastructure development, and long-term policy formulation. This initiative highlights the importance of integrating community-based mapping activities into rural development strategies to strengthen local governance and promote sustainable regional planning.